Necessity and Impossibility of Citizenship Education. Community of Philosophical Inquiry as a Resource to Overcome the Aporia (Foro de Educacion, 2016)
In Italy the expression «Cittadinanza e Costituzione», with which the citizenship education is denominated, makes reference to a plurality of leveles. In this article, at first, I sustain the thesis of the necessity of the citizenship education, underlining the constitutive connection between democracy and polite citizen and the urgency of it in this specific historical-social context. At second, I will be illustrated the dilemma of citizenship education: the circular paradox for which to educate active citizens it already needs to have some similar citizens. Paradox that it is connected to that of democracy, according to which it needs to have democratic citizens to have democracy. In the second part of the paper I will try to graze the dilemma, attenuating more than a premise. In the specific one, I will connect the citizenship education to the teaching of philosophy as social practice. The proposal will articulate on three levels: the philosophy for children in the primary school, the role of philosophy and human sciences in the secondary and the philosophy for community among the teachers.